Analisis Pengaruh Kualitas Kerja, Dukungan Tim, dan Budaya Organisasi terhadap Peningkatan Kinerja Pegawai dalam Lingkungan Kerja Profesional Berbasis Kolaborasi: Studi Kasus Dinas Pariwisata Ponorogo - Friska Adita Wulandari Putri; Umi Farida; Siti Chamidah (Jurnal Visi Manajemen, 2025)
The rapid development of globalization has significantly increased the utilization of technology and information, particularly in various organizational activities. This advancement impacts how organizations manage human resources to achieve optimal performance. This study aims to analyze the influence of work quality, team support, and organizational culture on the performance of employees at the Ponorogo Tourism Office. The research adopts a quantitative approach with a case study design. The population in this study comprises employees of the Ponorogo Tourism Office who hold civil servant status. Using a nonprobability sampling technique, a total of 42 respondents were selected as the research sample. Data collection was conducted through questionnaires, while data analysis employed multiple linear regression using the SPSS 25 program. The results of the partial (t-test) analysis show that work quality (p = 0.011), team support (p = 0.003), and organizational culture (p = 0.010) each have a positive and significant effect on employee performance. These findings indicate that employees who demonstrate high work quality, receive adequate support from their teams, and operate within a strong and positive organizational culture are more likely to exhibit better work performance. The research highlights the importance of maintaining high work standards, fostering collaboration among team members, and strengthening cultural values within the organization to improve employee performance outcomes. Practical implications suggest that the Ponorogo Tourism Office should focus on continuous professional development, effective teamwork strategies, and reinforcing organizational values to enhance productivity and service quality. This study contributes to the broader understanding of human resource management in the public sector, particularly within the tourism department, and serves as a reference for similar agencies seeking to optimize employee performance through organizational and interpersonal factors.